"Everyone is a potential leader" - attractiveness of a charismatic Church in Solo, Java (Indonesia) - Rodemeier, Susanne ("Każdy jest potencjalnym liderem" - atrakcyjność charyzmatycznego Kościoła w Solo, Jawa (Indonezja), 2012)
The evangelical-charismatic Family of God Church (GBI-KA: Gereja Bethel Indonesia - Keluarga Allah) was founded in the Javanese town of Solo and is currently booming, especially in predominantly Muslim surroundings. The reason why so many Christians prefer specifically this church over several other churches in town is still unknown. After doing ethnographic field research in 2011, I suggest that the reasons for its boom are not so much the economy or successful business relations, as was perhaps the case up tol five years ago. To prove my findings, I will take a closer look at the Family of God Church's economic and social system as well as its internal structure. It is quite obvious that this church, like many other churches, fills a gap in Indonesian social politics. But what is different about the Family of God Church is its inner cell-structure, which sees everyone as a potential leader. This structure picks up the idea of the International Charismatic Mission Church (ICMC) of G12 cell churches. The idea is to build an endlessly growing organism of cells and then add a spiritual component by organising these cells in groups of twelve to evoke the idea of Jesus and his twelve apostles. Next to the attractive spiritual component, this organisational structure stands out in contrast to the Javanese traditional social system as it offers individuals the chance to move up the hierarchical ladder. Furthermore, the masses of the fast growing population are broken down into small groups who share the same aim, i.e. to experience Jesus or to be "born again" (melahirkan kembali), as they call it.
Ekonomia = Economics, 2012, Nr 3 (20), s. 45-58
Keywords: Indonesia; church; religion; kościoły; religia